RELATIONSHIPS SCHOOL / FAMILY AND THE DIFFERENCES IN PERCEPTION FILIOPARENTAIS (Fiep Bulletin - online, 2011)
The Family and the School meet specific educational areas. Notwithstanding this, it is always possible and desirable collaboration between these two socializing institutions to contribute both to the emergence of true citizens, essential for building a modern, progressive and balanced country. Objectives: This study aims at understanding the phenomena that underlie the interaction between the Guardians and the School and to identify and characterize the perception that the students and Parents / Guardians retain representations of each other and of each relative to School Methodology: This quantitative study, exploratory, experimental and cross-sectional was based on two surveys for each questionnaire: one directed at students and others to their Guardians, in order to identify some of the child-parent and parent-child differences of perception and learn ways and conditions under which follows the involvement of parents in school life of students. The non-random sample consisted of 247 (65.3%) of the 645 students who represent the entire school population, with an average age of 13 years and a standard deviation of about 2 years and 133 (34.7%) of Guardians with an average age of 41 years and with a standard deviation of approximately 6 years. To perform the analysis was used the Pasw Statistics 18, and the level of significance (p) was maintained at 5%. Data analysis was performed by descriptive analysis, the T test for comparisons. Finally we proceed to factor analysis, to define the ideas of force investigations. Results: We detected that there are pronounced differences in perception between parents and children about school, and some parental attitudes that are perceived by their children in a way different from their parents and vice versa. Conclusions: Given the specificity of the study, the results confirm that low educational level of parents is presented as a difficulty to the appropriate school-family interaction; There are many differences of perception between parents and children about school, education of the children is mostly given to the mother; Most of the family structure is still the nuclear type, is not always beneficial participation of Parents in the work of children in general and Parents respect the teacher`s work.
Keywords: FAMILIY; SCHOOL; ADOLOSCENSE; PERCEPTION; AUTORITY